Peningkatan Kualitas Usaha Makanan Ringan Di Desa Gamping Tengah, Krian, Sidoarjo - Desrina Yusi Irawati; Agrienta Bellanov; Armadeo Ruben Canariesa; Cornelis Tredick Putra Pratama (Unika Santu Paulus Ruteng, 2024)
Gamping Village is a village in the Krian area, Sidoarjo, which is a busy route between cities. Several housewives there have businesses to support the family economy. One of the food businesses managed by Gamping village housewives is the